State of сoenopopulation of Cypripedium calceolus L. (Orchidaceae Juss.) in the Bukovynske Prykarpattya - A.I. Tokaryuk; I.I. Chornej (Інтродукція Рослин, 2009)
The results of research of the khorologycal, ecological, coenotical and population specialities of Cypripedium calceolus L. in the Bukovynske Prykarpattya are given.